EVALUATION OF HYDRAULIC FRACTURING STIMULATION USING MFRAC SIMULATOR AND MANUAL TO IMPROVE WELL PRODUCTIVITY "RR" - Rahmah Rahmah; Lia Yunita; Sari Wulandari (Petro : Jurnal Ilmiah Teknik Perminyakan, 2026)
This oil well is located in the "P" Field with a sandstone mineralogy type at a depth of 1784.5 - 1788 m. With an initial permeability of 9 mD and a porosity of 14%, suboptimal well productivity is the background for hydraulic fracturing. The initial planning stage using the MFrac simulator, namely the design of fracturing fluids, proppant and fracture geometry models used in the implementation stage. Next, collect some reservoir, production, well, rock mechanics data, and post job reports, for the evaluation stage from planning to implementation including step rate tests, mini frac, final design, and main frac. This evaluation stage determines the increase in formation permeability prices, productivity index (PI), decrease in skin prices and increase production flow rates. In the MFrac software, the fracture length was 218,876 ft, height 160,831 ft, width 0.034 ft, conductivity 4080 mD-ft, increase in average permeability was 285,000 mD and skin value was -5,980, increase in PI value to 1,214 Bpd/psi, and increase in total flow rate 869 BFPD and oil flow rate 616.99 BOPD, from IPR 2 phase Vogel value J/Jo 29 times, and it is considered that this hydraulic fracturing was successful.